A case report of anterior mediastinal signet ring cell carcinoma. Issue 48 (2nd December 2022) - Liu, Simin; Zhao, Anbang; Mao, Ming
Abstract : Rationale: Anterior mediastinal signet ring cell carcinoma (SRCC) is a rare tumor that has only been reported in two cases of thymic cancer. Positive immunohistochemistry (IHC) staining for caudal-type homeobox (CDX) 2, cytokeratin (CK) 20 and special AT-rich binding protein (SATB) 2 usually indicate gastrointestinal tumors but begin to appear in thymic cancers with enteric differentiation. Here, we describe a case of the anterior mediastinal SRCC with enteric differentiation who was correctly treated with surgery and chemo-radiation and was alive after four months. Patient concerns: A 48-year-old female presented without chest and lung symptoms had an anterior mediastinal mass during a routine physical examination. Laboratory examinations showed an elevated level of serum carbohydrate antigen (CA)-125 at 73.63 U/mL. Chest computed tomography (CT) showed an irregular soft tissue density shadow with heterogeneous enhancement in the anterior mediastinum. The tumor had invaded the pericardium, the left septal nerve and the innominate and was completely removed after anterior mediastinal surgery. Postoperative pathological examinations revealed signet ring cell features and positive staining for CDX2, CK20, SATB2 and Ki-67 (Li: 70%). The samples were negative for cluster of differentiation (CD)-5, CK7, thyroid transcription factor (TTF) 1, NapsinA, CerbB-2, P53 and PD-L1 by IHC examinations. The suspected diagnosis was an anterior mediastinal SRCC that had originated in the digestive system. Diagnosis: The patient was diagnosed with anterior mediastinal SRCC. Interventions: The patient was treated with surgery and combined chemo-radiotherapy. Outcomes: The patient had no recurrence or metastasis after five months. Lessons: We describe a rare case of the anterior mediastinal SRCC of unknown origin. Our case, for the first time shows that surgery combined with chemo-radiotherapy is an effective treatment regimen for anterior mediastinal SRCC.